Virus and cytotoxic T lymphocytes: crucial role of viral peptide secondary structure in major histocompatibility complex class I interactions. - Gairin, J E (1993)
Viral antigens are presented to cytotoxic T lymphocytes (CTLs) by H-2-restricted major histocompatibility complex (MHC) glycoproteins. Binding of the endogenously processed viral peptides (epitopes) to their specific MHC molecules is an early intracellular event in the recognition process and is necessary for subsequent killing of virus-infected cells by virus-specific CTLs. It is now well established that interaction between a viral antigenic peptide and MHC is dependent on the primary structure (length and amino acid sequence) of that antigen. Here we show, using the H-2Db-restricted epitope GP277-286 of lymphocytic choriomeningitis virus as a model, that the secondary structure (conformation) of the viral sequence also plays a crucial role in the binding of a viral antigen to MHC glycoprotein and in its subsequent presentation to virus-specific CTLs.